1987
DOI: 10.1089/dna.1987.6.373
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Recombination Directed by Single-Stranded Crossover Linkers: Specific Deletion of the Amino-Terminal Region of the β-Galactosidase Gene in pUC Plasmids

Abstract: The "duplex crossover linker" technique was simplified and used to delete the beta-galactosidase (beta-Gal)-coding sequence upstream from the multiple restriction sites in pUC plasmids. A single-stranded crossover linker, with a homology-searching sequence as short as 5 bases, was initially ligated to a linearized plasmid. Inside Escherichia coli, the plasmid was circularized by intramolecular, homologous recombination between the (5'-or 3'-) protruding homology-searching sequence and a targeted region in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…6). This finding is consistent with a previous suggestion that a 5-bp homologous sequence is sufficient to generate recombination between single-stranded plasmid DNA fragments (29). Hybrid proteins BD701, BD725, and BD742 were apparently generated following homologous recombination of linearized plasmid molecules which were not ligated prior to transformation.…”
Section: Discussionsupporting
confidence: 92%
“…6). This finding is consistent with a previous suggestion that a 5-bp homologous sequence is sufficient to generate recombination between single-stranded plasmid DNA fragments (29). Hybrid proteins BD701, BD725, and BD742 were apparently generated following homologous recombination of linearized plasmid molecules which were not ligated prior to transformation.…”
Section: Discussionsupporting
confidence: 92%
“…An in vivo DNA polymerization would subsequently repair the gap at the single-stranded region to yield a circular plasmid with nicks. However, this ability to direct in vivo DNA polymerization appeared to be limited, as it failed to generate mutants if the gap to be filled in was wider than 22 bases, as shown in other studies (Sung et al, 1989;Sung & Zahab, 1987). This limited capability indicated that the initial exonucleolytic reaction may be controlled or directed (Radding, 1973;Cassuto & Radding, 1971) such that the degradation would not be so extensive as to generate a gap which was too wide to be repaired.…”
Section: Discussionmentioning
confidence: 94%
“…The resultant plasmid pProPTH-1 still maintained a residual /3-Gal sequence fused with the ProPTH gene. The second cross-over linker, COL-3 (Sung & Zahab, 1987), with a 22-base homology-searching sequence targeting the ribosome-binding site of the lacZ gene, efficiently deleted the /3-Gal gene residue to yield plasmid pProPTH-1 B. The restored £coRI site of pProPTH-1 B was eliminated by linearization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation